Growth Dynamics: The Myth of Economic Recovery: Comment - Mueller, Hannes (American Economic Review, 2012)
This comment highlights different ways of coding crisis episodes in Cerra and Saxena (2008) (CS). The comment shows that the coding used for civil war implies a misrepresentation of its impact. A correct coding of civil war reveals that the average civil war leads to a loss in output of 18 percent. This makes civil wars more devastating than all other crisis studied by CS.